Comparison of monomeric anthocyanins and colour stability of fresh, concentrate and freeze-dried encapsulated cherry juice stored at 38º C - Sanchez, Virginia (2015)
Fil: Sanchez, Virginia. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina